The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41380-021-01271-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-genetic findings in 509 frontotemporal dementia patients

Abstract: Frontotemporal dementia (FTD) is a clinically and genetically heterogeneous disorder. To which extent genetic aberrations dictate clinical presentation remains elusive. We investigated the spectrum of genetic causes and assessed the genotype-driven differences in biomarker profiles, disease severity and clinical manifestation by recruiting 509 FTD patients from different centers of the German FTLD consortium where individuals were clinically assessed including biomarker analysis. Exome sequencing as well as C9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…Among FTDs, the behavioural variant (bvFTD) is the most prevalent phenotype associated with MNDs ( Saxon et al, 2017a , b ; Wagner et al, 2021 ): the co-occurrence of MND or UMN/LMN dysfunction and bvFTD has been indeed thoroughly explored ( Ahmed et al, 2021 ). By contrast, little is still known about the pathology, genetics and clinical features of co-occurring primary progressive aphasia (PPA) and MND ( Ulugut et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among FTDs, the behavioural variant (bvFTD) is the most prevalent phenotype associated with MNDs ( Saxon et al, 2017a , b ; Wagner et al, 2021 ): the co-occurrence of MND or UMN/LMN dysfunction and bvFTD has been indeed thoroughly explored ( Ahmed et al, 2021 ). By contrast, little is still known about the pathology, genetics and clinical features of co-occurring primary progressive aphasia (PPA) and MND ( Ulugut et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The elevated levels of ABCA2 and ABCA7 in FTLD-TDP reported here could be critical to compensatory mechanisms. Interestingly, rare variants of the ABCA7 gene have been identified in two sporadic cases of FTD ( Ciani et al, 2019 ) and a homozygous loss-of-function ABCA7 variant was also identified, suggesting ABCA7 as a candidate gene for monogenic FTD ( Wagner et al, 2021 ). A partial deletion in the ABCA7 gene and a variant in the GRN gene has been found in a patient with semantic variant of primary progressive aphasia ( Antonell et al, 2020 ), one of the clinical phenotypes associated with FTLD-TDP.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis results had been not available for single subjects in our study. However, a recent study ( Wagner et al, 2021 ) involving partly overlapping 509 patients with bvFTD and PPA from the FTLD consortium study revealed by exome sequencing as well as C9orf72 repeat analysis that 18.1 % did show pathogenic variants, without any impact of distribution of APOE alleles. Note that necessary fulfillment of operationalized clinical criteria as a precondition for inclusion in our study prevented from circular approaches regarding imaging.…”
Section: Methodsmentioning
confidence: 99%